Consolidation Behaviour of Dredged Marine Soils Considering the Incorporation of Granular Drainage Layer - Siti Farhanah, SM Johan; Chee Ming, Chan (IOP Publishing Ltd, 2020)
The extraction of DMS from seabed along the Malaysian coastal generate millions cubic meters every year. Dredge-transport-dump the DMS at the specified open waters are unfavourable in context of environmental and geotechnical engineering. This paper describes consolidation behaviour of DMS using a modified large- oedometer with a layer of recycled granular materials such as palm oil clinker and recycled pavement materials. DMS were obtained to have high ratio of Wc with 3.27LL and considered as silty clay. A layer of drainage materials accelerates the rate of consolidation and changes in hydraulic conductivity, k of DMS. At the end of consolidation, both RPM and POC layer expediate the water from DMS and it becomes stiffer and structured.